Affect and attention after Deleuze and Whitehead ecological attunement - Duvernoy, Russell J. (New perspectives in ontology., 2021)
Drawing on recent work by Massumi, Stengers, Debaise and Williams, this book explores their work in relation to other speculative trends in recent philosophy, including new materialisms, posthumanisms, speculative realism and object-oriented-ontology.